Success Case Method (Better Evaluation)
The Success Case Method (SCM) involves identifying the most and least successful cases in a program and examining them in detail. This appro ach was developed by Robert Brinkerhoff to assess the impact of organi zational interventions, such as training and coaching, though the use of SCM is not limited to this context. It is a useful approach to docu ment stories of impact and to develop an understanding of the factors that enhance or impede impact. The Success Case Method deliberately lo oks at the most, and least, successful participants of a program. The purpose is not to examine the average performance - rather, by identif ying and examining the extreme cases, it asks: 'When the program works , how well does it work? What is working, and what is not?'.